一个极限证明

求证:$\displaystyle \lim\limits_{x\to 0+}\sum\limits_{n=1}^{\infty}\frac{(-1)^n}{n^x}=-\frac{1}{2}.$
已邀请:
$\Gamma(s)=\int_0^{\infty}x^{s-1}e^{-x}dx=\int_0^{\infty}(at)^{s-1}e^{-at}dat=a^s\int_0^{\infty}t^{s-1}e^{-at}dt$

$a^{-s}=\frac{1}{\Gamma(s)}\int_0^{\infty}t^{s-1}e^{-at}dt$

$\sum\limits_{n=1}^{\infty}\frac{(-1)^n}{n^s}=\frac{1}{\Gamma(s)}\int_0^{\infty}t^{s-1}\sum\limits_{n=1}^{\infty}(-1)^ne^{-nt}dt=\frac{1}{\Gamma(s)}\int_0^{\infty}t^{s-1}\frac{-e^{-t}}{1+e^{-t}}dt=-\frac{1}{\Gamma(s)}\int_0^{\infty}\frac{t^{s-1}}{1+e^t}dt$

$-\sum\limits_{n=1}^{\infty}\frac{(-1)^n}{n^s}=\cfrac{\int_0^{\infty}\frac{t^{s-1}}{1+e^t}dt}{\int_0^{\infty}x^{s-1}e^{-x}dx}=\cfrac{\int_0^{\delta}\frac{t^{s-1}}{1+e^t}dt+\int_{\delta}^{\infty}\frac{t^{s-1}}{1+e^t}dt}{\int_0^{\delta}x^{s-1}e^{-x}dx+\int_{\delta}^{\infty}x^{s-1}e^{-x}dx}$

$\cfrac{\int_0^{\delta}\frac{t^{s-1}}{1+e^{\delta}}dt+\int_{\delta}^{\infty}\frac{t^{s-1}}{1+e^t}dt}{\int_0^{\delta}x^{s-1}dx+\int_{\delta}^{\infty}x^{s-1}e^{-x}dx}\le-\sum\limits_{n=1}^{\infty}\frac{(-1)^n}{n^s}\le\cfrac{\int_0^{\delta}\frac{t^{s-1}}{2}dt+\int_{\delta}^{\infty}\frac{t^{s-1}}{1+e^t}dt}{\int_0^{\delta}x^{s-1}e^{-\delta}dx+\int_{\delta}^{\infty}x^{s-1}e^{-x}dx}$

$s\to 0^+$
$\frac{1}{1+e^{\delta}}\le\liminf_{s\to 0^+}-\sum\limits_{n=1}^{\infty}\frac{(-1)^n}{n^s}\le\limsup_{s\to 0^+}-\sum\limits_{n=1}^{\infty}\frac{(-1)^n}{n^s}\le\frac{e^{\delta}}{2}$

$\delta\to 0^+$
$\lim\limits_{s\to 0^+}\sum\limits_{n=1}^{\infty}\frac{(-1)^n}{n^s}=-\frac12$

隐身守候

赞同来自:

转化为幂级数的形式可以求解

要回复问题请先登录注册